2016
DOI: 10.1007/s11571-016-9410-4
|View full text |Cite
|
Sign up to set email alerts
|

Semantic integration by pattern priming: experiment and cortical network model

Abstract: Neural network models describe semantic priming effects by way of mechanisms of activation of neurons coding for words that rely strongly on synaptic efficacies between pairs of neurons. Biologically inspired Hebbian learning defines efficacy values as a function of the activity of pre-and post-synaptic neurons only. It generates only pair associations between words in the semantic network. However, the statistical analysis of large text databases points to the frequent occurrence not only of pairs of words (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 122 publications
(180 reference statements)
0
11
0
Order By: Relevance
“…This ability to extract the combination of two preceding items to better predict the following one takes the form of a quite complex computational representation of probability values. Such learning of second-order TP challenges our understanding of combinatorial learning [ 32 , 33 ]. Biologically inspired models of learning encode transitional probability through the efficacy of synapses [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This ability to extract the combination of two preceding items to better predict the following one takes the form of a quite complex computational representation of probability values. Such learning of second-order TP challenges our understanding of combinatorial learning [ 32 , 33 ]. Biologically inspired models of learning encode transitional probability through the efficacy of synapses [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental design consisted of four triplets of the form X − Y − Z that combined items according to an XOR logic [ 33 ]. The XOR allows us to dissociate between first-order TPs ( p ( Y | X ), p ( Z | Y ), and p ( Z | X )) and second-order TPs p ( Z | XY ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Kambe et al (2015) suggested that beta phase resetting occurred in areas related to the subsequent stimulus, supporting the idea that the perception of multisensory stimuli is simultaneous. Neural network models have been argued to describe semantic priming effects by activating neurons that code for words that rely strongly on synaptic efficacies between pairs of neurons (Lavigne et al 2016).…”
Section: Introductionmentioning
confidence: 99%